The Analysis of Polyamine Mud Application in Drilling Claystone and Shale in ES Field - Tony, Brian; Saputra, Ega Dimas; Astuti, Dian Indri (Journal of Earth Energy Science, Engineering, and Technology, 2025)
Historically, the ES Field is a drilling area located in South Sumatera Basin that applies 10% KCl Polymer throughout the drilling section. Challenges such as pipe sticking and increased borehole diameter due to washout have been encountered in this field. Increased cement volume and tripping time are factors affecting drilling efficiency. Therefore, innovation and improvement in the type of drilling mud used are needed to address these challenges in the field. This paper discusses the effectiveness of polyamine through shale study analysis, including CEC, dispersion, accretion, XRD, and LSM, as well as performance analysis of mud application as an alternative to KCl-Polymer in the drilling of Well ED-24 in the ES Field. Results indicate that polyamine has advantages and benefits as an inhibitor. Shale study from the cuttings of Well ED-22 shows that shale in the Gumai Formation is characterized by kaolinite and is dispersive, hence the use of polyamine. In the 17.5-inch trajectory, tight hole issues were found due to swelling clay at a depth of 561 mMD, which had not occurred previously with 10% KCl-Polymer mud. In the 12.25-inch trajectory, the main cause of shale collapse was insufficient mud weight. Overall, polyamine mud effectively suppresses solid dispersion into the mud, prevents balling, and addresses hole cleaning issues during drilling. The use of 10% KCl-Polymer can be reconsidered for subsequent drilling in the Air Benakat claystone formation, while polyamine mud remains relevant and should be considered for drilling the dispersive Gumai shale formation to suppress solid dispersion.